2023
DOI: 10.1002/anie.202213297
|View full text |Cite
|
Sign up to set email alerts
|

A Visible Light Driven Nickel Carbonylation Catalyst: The Synthesis of Acid Chlorides from Alkyl Halides

Abstract: We describe here the development of a visible light driven nickel carbonylation catalyst. The combination of the large bite-angle Xantphos ligand with nickel-(0) generates a catalyst capable of activating alkyl halides toward carbonylation at ambient temperature in the presence of blue light irradiation, and the reductive elimination of high energy acid chloride products. Unlike classical carbonylations, where the coordination of carbon monoxide inhibits the reactivity of earth abundant nickel catalysts, a CO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…In 2022, Arndtsen and coworkers reported a visible‐light driven synthesis of acid chlorides under mild conditions (Scheme 16). [ 30 ] As previously mentioned, nickel catalyzed carbonylative reactions typically require high temperatures and activated aryl halide substrates due to the relatively high affinity of nickel to CO. However, taking inspiration from the visible‐light excitation of palladium catalysts like [Pd(allyl)Cl] 2 , Arndtsen designed a method to synthesize acid chlorides from alkyl halides through visible‐light driven nickel‐catalyzed carbonylation.…”
Section: Nickel Catalyzed Carbonylation With Co Gas As the Carbonyl S...mentioning
confidence: 99%
“…In 2022, Arndtsen and coworkers reported a visible‐light driven synthesis of acid chlorides under mild conditions (Scheme 16). [ 30 ] As previously mentioned, nickel catalyzed carbonylative reactions typically require high temperatures and activated aryl halide substrates due to the relatively high affinity of nickel to CO. However, taking inspiration from the visible‐light excitation of palladium catalysts like [Pd(allyl)Cl] 2 , Arndtsen designed a method to synthesize acid chlorides from alkyl halides through visible‐light driven nickel‐catalyzed carbonylation.…”
Section: Nickel Catalyzed Carbonylation With Co Gas As the Carbonyl S...mentioning
confidence: 99%
“…Following their reports on visible‐light excitation of palladium to drive both oxidative addition and reductive elimination in carbonylation reactions, [ 47 ] Arndtsen and co‐workers recently developed a visible light driven nickel‐catalyzed carbonylation of alkyl halides for the synthesis of acyl chlorides (Scheme 22). [ 48 ] The combination of the large bite‐angle Xantphos ligand with nickel(0) generated a catalyst capable of activating alkyl halides toward carbonylation at ambient temperature in the presence of blue light irradiation. Primary, secondary, tertiary alkyl iodides and activated alkyl bromides were all applicable to give the build‐up reactive acyl chlorides in good yields.…”
Section: Carbonylative C—x Coupling Of Alkyl Electrophilesmentioning
confidence: 99%
“…Under the blue light/Ni system reported by Arndtsen et al, a previously successful alkene-tethered aryl iodide reacted and gave the carboiodinated product in 60% yield (Table , entry 2). We screened a variety of ligands and found that diphenylphosphinopropane (DPPP) gave a higher yield (entry 1).…”
mentioning
confidence: 95%
“…26 A potential solution to this problem arose based on a recent report by the Arndtsen group using nickel/XantPhos complexes as a photocatalyst for the carbonylation of alkyl halides (Scheme 1c). 27 Unlike traditional nickel photocatalysis that can undergo MLCT with highly conjugated ligands, the use of a nickel phosphine complex as a photocatalyst facilitated a unique reaction pathway that might overcome the limitations. 28 Herein, we describe a photoinduced nickel-catalyzed carbohalogenation reaction via reversible C−X bond formation (Scheme 1d).…”
mentioning
confidence: 99%